Tashmimul Al’ab Al Lughowiyah Min Kitab Al Arabiyah Baina Yadaik (Al Wahdah 1-8) Minal Kitab Al Awwal) Litanmiati Maharatil Kalam Lada Tholibat Al Fashlus Sabi’ Bima’had Muhammadiyah ‘Abdur Razzaq Fachruddin As Sanah Ad Dirosiah 2022/2023 - Sumiati; Nashirudin, Muh (Ukazh: Journal of Arabic Studies, 2023)
The aim of this research is (1) to develop an Arabic language game design to improve the speaking skills of seventh grade students at PPM MBS Ar-Fachrudin Yogyakarta. (2) Knowing the characteristics of game design after being implemented in the educational process. (3) Knowing the effectiveness of the game design. Researchers use empirical field studies to develop their research, using development research methods in the ADDIE model (analysis, design, development, implementation and evaluation). Data collection methods in this research are observation, interviews, questionnaires and tests. The research sample was seventh grade students, ten samples were taken as the control group and ten samples as the experimental group. The results of the research show that the educational material is effective for improving speaking skills in the seventh semester, depending on the results obtained for the post-test, the researcher found that the degree of t-account (t_o) in this study (0.8) was greater than the degree of t-table (t_t) at the level of 0.04